An Overview and Evolution of the Intelligent Transportation System as VANETs (International Journal of Engineering and Computer Science, 2017)
Vehicular Ad-hoc Network (VANET) in the recent years have emerged as a most attractive topic for researchers and automotive industries due to their tremendous potential to improve traffic safety, efficiency and other added services.The routing in VANET is the most challenging part of research. In this paper we have discussed the various routing protocols and also discussed the advantages as well as the disadvantages of these routing protocols.